miR-26a-5p Attenuates Oxidative Stress and Inflammation in Diabetic Retinopathy through the USP14/NF-κB Signaling Pathway - Jie Bian; Weizhong Ge; Zhengmei Jiang (Journal of Ophthalmology)
Purpose. Diabetic retinopathy (DR) is an ocular disease caused by diabetes and may lead to vision impairment and even blindness. Oxidative stress and inflammation are two key pathogenic factors of DR. Recently, regulatory roles of different microRNAs (miRNAs) in DR have been widely verified. miR-26a-5p has been confirmed to be a potential biomarker of DR. Nevertheless, the specific functions of miR-26a-5p in DR are still unclear. Methods. Primary cultured mouse retinal Müller cells in exposure to high glucose (HG) were used to establish an in vitro DR model. Müller cells were identified via morphology observation under phase contrast microscope and fluorescence staining for glutamine synthetase. The in vivo animal models for DR were constructed using streptozotocin-induced diabetic C57BL/6 mice. Western blotting was performed to quantify cytochrome c protein level in the cytoplasm and mitochondria of Müller cells and to measure protein levels of glial fibrillary acidic protein (GFAP), ubiquitin-specific peptidase 14 (USP14), as well as factors associated with NF-κB signaling (p-IκBα, IκBα, p-p65, and p65) in Müller cells or murine retinal tissues. ROS production was detected by CM-H2DCFDA staining, and the concentration of oxidative stress markers (MDA, SOD, and CAT) was estimated by using corresponding commercial kits. Quantification of mRNA expression was conducted by RT-qPCR analysis. The concentration of proinflammatory factors (TNF-α, IL-1β, and IL-6) was evaluated by ELISA. Hematoxylin-eosin staining for murine retinal tissues was performed for histopathological analysis. Immunofluorescence staining was conducted to determine NF-κB p65 nuclear translocation in Müller cells. Furthermore, the interaction between miR-26a-5p and USP14 was verified via the luciferase reporter assays. Results. HG stimulation contributed to Müller cell dysfunction by inducing inflammation, oxidative injury, and mitochondrial damage to Müller cells. miR-26a-5p was downregulated in Müller cells under HG condition, and overexpression of miR-26a-5p relieved HG-induced Müller cell dysfunction. Moreover, miR-26a-5p targeted USP14 and inversely regulated USP14 expression. Additionally, HG-evoked activation of NF-κB signaling was suppressed by USP14 knockdown or miR-26a-5p upregulation. Rescue assays showed that the protective impact of miR-26a-5p upregulation against HG-induced Müller cell dysfunction was reversed by USP14 overexpression. Furthermore, USP14 upregulation and activation of NF-κB signaling in the retinas of DR mice were detected in animal experiments. Injection with miR-26a-5p agomir improved retinal histopathological injury and weakened the concentration of proinflammatory cytokines and oxidative stress markers in the retinas of DR mice. Conclusion. miR-26a-5p inhibits oxidative stress and inflammation in DR progression by targeting USP14 and inactivating the NF-κB signaling pathway.